RANCANG BANGUN MESIN PENGHANCUR KACA - Bethony, Christoper Jamesingli Sapan; Saleh, Agus (Jurnal Mahasiswa Terapan; Vol 2 No 1 (2025): Jurnal Mahasiswa Terapan, 2025)
The waste problem in Indonesia, especially in major cities with high population density, has become an increasingly urgent issue to address. Waste, which is generally considered dirty, foul-smelling, and potentially disease-causing as well as environmentally damaging, can actually be turned into a business opportunity through recycling processes with the right technology. This research aims to design and produce a glass bottle crushing machine with a capacity of 4 kg/minute as a solution for glass bottle waste management. The machine uses a 2800 rpm electric motor as the drive, blades made of steel plate, and a frame made of hollow iron. Testing was conducted using glass bottle waste to determine the effectiveness of the machine. The test results show that the longer the crushing time, the finer the glass fragments produced. For a 1 kg load crushed for 1 minute, the average fragment size was 7 mm; for 2 minutes, it was 4.5 mm; and for 3 minutes, it was 1.7 mm. Thus, this machine is effective in processing glass bottle waste into small fragments that can be reused.